Antioxidant and anti-inflammatory activities of quercetin and its derivatives - Lesjak, Marija; Beara, Ivana; Simin, Nataša; Pintać, Diandra; Majkić, Tatjana; Bekvalac, Kristina; Orčić, Dejan; Mimica-Dukić, Neda (Journal of functional foods, 2018)
•Antioxidant and anti-inflammatory activities of quercetin derivatives were studied.•Quercetin metabolites present in systemic circulation have potent biopotential.•Derivatization quercetin resulted in decrease of antioxidant activity.•Derivatization of quercetin does not significantly defines anti-inflammatory potential.•Metabolites should be included in defining biopotential of quercetin-rich diet. Quercetin is hardly bioavailable and largely transformed to different metabolites. Although little is known about their biological activities, these metabolites are crucial for explanation of health benefits associated with quercetin dietary intake. In this study, the antioxidant and anti-inflammatory activities of six quercetin derivatives (quercetin-3-O-glucuronide, tamarixetin, isorhamnetin, isorhamnetin-3-O-glucoside, quercetin-3,4′-di-O-glucoside, quercetin-3,5,7,3′,4′-pentamethylether) were compared with the activity of common onion extract as the main source of dietary quercetin and standards (butylated hydroxytoluene and aspirin). The quercetin derivatives demonstrated notable bioactivities, similar to standards and onion. Derivatization of quercetin hydroxyl groups resulted in decrease of antioxidant potency. However, the number of quercetin free hydroxyl groups was not in direct correlation with its potential to inhibit inflammatory mediators production. To conclude, quercetin derivatives present in systemic circulation after consumption of quercetin may act as potent antioxidant and anti-inflammatory agents and can contribute to overall biological activity of quercetin-rich diet.